A Review of Nuclear War: A Scenario by Annie Jacobsen - Simon Bennett (The Journal of Intelligence, Conflict and Warfare)
Annie Jacobsen’s book is simultaneously a linear account of a nuclear decapitation strike on the United States, a historical account of the development of fission and fusion weapons and the doctrines that inform their development, deployment and use and a scientific account of the consequences for life on earth of a global thermonuclear war. Jacobsen’s bestselling book is both gripping and helpful to those seeking a clearer understanding of the role that nuclear arsenals play in today’s turbulent geopolitics.